Geografia do trânsito: análise geográfica da mortalidade em acidentes de trânsito no município de Vila Velha-ES, entre 2005 a 2015 - Nunes, Giovani de Salles (2018)
According to data from the World Health Organization - WHO (2016), traffic accidents are responsible for the mortality of 1.25 million people in the world each year and its reduction is of concern to all countries. Strategic measures taken by the rulers and planners of both the urban and social spheres are very important to meet their objectives, which are the reduction and minimization of the impacts caused by traffic accidents. However, for this purpose, it is necessary to identify the places of greatest occurrence traffic accidents, as well as their dynamics and their characteristics such as their typology, the months, the days and the times they occur, as well as the factors that contribute to its occurrence. With this purpose, the present research sought to address the spatialisation of traffic accidents with fatalities in the municipality of Vila Velha-ES in the period between 2005 and 2015, aiming to understand the dynamics and characteristics of these accidents in the municipality, using geographic information system (GIS) tools to identify the main areas with the highest concentration of accidents and after this identification, from the compilation with statistical data of several sources such as DATASUS, DETRAN, IBGE, PRF and SESPES, to analyze precisely the configuration of these accidents according to their temporal and spatial incidence. With this, it is possible to recognize the factors that contributed to their occurrence and from there propose measures for an effective reduction of these accidents, which can serve as a basis for the implementation of programs by the Municipality of Vila Velha, other city halls and State Government or for future studies in the area of geography, related areas and other sciences that approach the subject